Lung cancer and cigarette smoking in women: a multicenter case-control study in Europe. - Agudo, A; Ahrens, W; Benhamou, E; Benhamou, S; Boffetta, P; Darby, S; Forastiere, F; Fortes, C; Gaborieau, V; González, C; Jöckel, K; Kreuzer, M; et al. (2000)
The association between cigarette smoking and lung cancer risk in women was investigated within the framework of a case-control study in 9 centres from 6 European countries. Cases were 1,556 women up to 75 years of age with histologically confirmed primary lung cancer; 2, 450 controls with age distribution similar to cases were selected. The predominant cell type was adenocarcinoma (33.5%), with similar proportions for squamous-cell type (26.4%) and small-cell carcinoma (22.3%). Overall, smoking cigarettes at any time was associated with a 5-fold increase in lung cancer risk (odds ratio 5.21, 95% confidence interval 4.49-6.04); corresponding figures for current smoking habits were 8.94, 7.54-10.6. The association showed a dose-response relationship with duration of the habit and daily and cumulative lifetime smoking. A significant excess risk of 70% was associated with every 10 pack-years smoked. After 10 years of smoking cessation, the relative risk decreased to 20% compared to current smokers. The following characteristics were associated with a higher relative risk: inhalation of smoke, smoking non-filter cigarettes, smoking dark-type cigarettes and starting at young age. The association was observed for all major histological types, being the strongest for small-cell type carcinoma, followed by squamous-cell type and the lowest for adenocarcinoma. The proportion of lung-cancer cases in the population attributable to cigarette smoking ranged from 14% to 85%. We concluded that women share most features of the association between cigarette smoking and lung cancer observed in men.